Clinical manifestations and diagnosis of acute myeloid leukemia in a patient with a medical history of pulmonary tuberculosis (a case report) - O. M. Raznatovska; O. S. Shalmin; S. B. Noreiko (Zaporožskij Medicinskij Žurnal)
The aim is to familiarize practitioners with the initial clinical manifestations of acute myeloid leukemia and its diagnosis in a patient with a past medical history of pulmonary tuberculosis.